Measurement of beauty production via non-prompt D0 mesons in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Adamová, Dagmar; Adler, A.; Adolfsson, Jonatan; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; et al. (Journal of high energy physics, 2022)
The production of non-prompt D0 mesons from beauty-hadron decays was measured at midrapidity (|y| < 0.5) in Pb-Pb collisions at a nucleon-nucleon center-of-mass energy of $$ \sqrt{{s}_{NN}} $$= 5.02 TeV with the ALICE experiment at the LHC. Their nuclear modification factor (RAA), measured for the first time down to pT = 1 GeV/c in the 0-10% and 30-50% centrality classes, indicates a significant suppression, up to a factor of about three, for pT > 5 GeV/c in the 0-10% central Pb-Pb collisions. The data are described by models that include both collisional and radiative processes in the calculation of beauty-quark energy loss in the quark-gluon plasma, and quark recombination in addition to fragmentation as a hadronisation mechanism. The ratio of the non-prompt to prompt D0-meson RAA is larger than unity for pT > 4 GeV/c in the 0-10% central Pb-Pb collisions, as predicted by models in which beauty quarks lose less energy than charm quarks in the quark-gluon plasma because of their larger mass.